Aristotle's Metaphysics Alpha Symposium Aristotelicum - Symposium Aristotelicum 2008 : Leuven, Belgium); Steel, Carlos G.; Primavesi, Oliver (Oxford : Oxford University Press, 2012)
This is a key text for the reconstruction of the early history of Greek philosophy, and sets the agenda for Aristotle's project of wisdom. Included is a new edition of the Greek text, and an introduction which examines its divergent traditions.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Aristotle. -- Congresses; Metaphysics -- Congresses